Disclosure of Information in Environmental Documents in Supporting the Role of Public Monitoring - I Made Gemet Dananjaya Suta; I Gusti Agung Mas Prabandari; Ni Luh Gede Astariyani (Universitas Airlangga, 2021)
The role of the community is important in realising the fulfilment of the right to a good and healthy environment as part of human rights. Lack of awareness of the disclosure of information in environmental documents to the public in surveilling activities or businesses that impact the environment is one of the many violations of environmental law resulting in environmental damage and pollution. This paper examines the importance of information disclosure in environmental documents in supporting the role of community oversight of activities that impact the environment. It used a normative legal research method with the statutory and conceptual approaches. This paper finds that the disclosure of information in environmental documents is important in optimising the role of public monitoring. Environmental documents are used as a guide for detailed information related to compliance with the implementation of activity on its terms and obligations. Such disclosure can be seen as the implementation of the right to access information in support of community responsibility, guaranteeing and fulfilling the right to a good and healthy environment as a human right so that environmental damage and pollution from activities that are illegal and/or violate environmental permits can be controlled and prevented.